Qualitative Behaviors of Functional Differential Equations of Third Order with Multiple Deviating Arguments - Cemil Tunç (Abstract and Applied Analysis)
This paper considers nonautonomous functional differential equations of the third order with multiple constant deviating arguments. Using the Lyapunov-Krasovskii functional approach, we find certain sufficient conditions for the solutions to be stable and bounded. We give an example to illustrate the theoretical analysis made in this work and to show the effectiveness of the method utilized here.